2013
DOI: 10.1524/ract.2013.2022
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Np(IV) complexes with gluconic acid under alkaline conditions: sorption studies

Abstract: The complexation of Np(IV) with gluconic acid (GLU) under alkaline conditions was investigated in the absence of Ca by carrying out a series of sorption experiments. The decrease of Np(IV) sorption on the sorbing material at increasing concentrations of GLU was interpreted as the formation of Np(IV)-GLU aqueous complexes. The modelling of experimental data according to the Schubert method [1] confirmed the formation of a complex with a Np : GLU ratio 1 : 1. The stoichiometry of the complex Np(OH)4GLU− was prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…In addition, the sorption behaviour of Np(IV) and Np(VI) on C-S-H phases observed in the present experiments (see section 3.3) is similar to the sorption behaviour of Th(IV) and U(VI) onto C-S-H phases reported in the literature [27,41]. i.e., the d values for Np(IV) and Th(IV) sorption on C-S-H phases are both independent of the C:S ratio whereas d values for Np(VI) and the U(VI) sorption both decrease with increasing C:S ratio.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the sorption behaviour of Np(IV) and Np(VI) on C-S-H phases observed in the present experiments (see section 3.3) is similar to the sorption behaviour of Th(IV) and U(VI) onto C-S-H phases reported in the literature [27,41]. i.e., the d values for Np(IV) and Th(IV) sorption on C-S-H phases are both independent of the C:S ratio whereas d values for Np(VI) and the U(VI) sorption both decrease with increasing C:S ratio.…”
supporting
confidence: 90%
“…Gaona et al [19,22] and Rojo et al [41] showed that Na-dithionite and Na-hypochlorite have no influence on the sorption behaviour of tetravalent and hexavalent actinides. XANES spectra of C-S-H pastes containing much higher…”
Section: Experimental Set-upmentioning
confidence: 99%
“…In being structurally similar, Gluc À has been widely used as a readily available analogue for -Isa À , for which extraction and purification has been challenging and time consuming (Glaus et al, 2006;Giroux et al, 2002;Tits et al, 2005;Zhang et al, 2007;Zhang et al, 2009;Colà s et al, 2013a,b;Rojo et al, 2013;Dudá s et al, 2017). It has been recently shown though, that there are some fundamental differences between the complexing properties of the two ligands in alkaline medium in the presence of calcium (Dudá s et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[70] The concentration of Glucin cement pore waters may range from 10 -5 to 10 -2 M, [101] which is several orders of magnitude lower than that of α-Isa -, which could reach as high as 0.1 M. [85] As the preparation and purification of Isais rather time consuming, Gluc -, being structurally similar, has been widely used as a readily available analogue for Isa -. [102][103][104][105][106][107][108][109] Birjkumar et al, however, scrutinized the similarities between Isaand Glucin U(VI) chemistry and suggested that caution should be exercised when using Glucas a thermodynamic model for Isain such systems. [110] Both Isaand Gluchave been shown to be effective complexing agents in the presence of actinides and lanthanides.…”
Section: Importance Of Complexing Agentsmentioning
confidence: 99%
“…[107] In highly alkaline medium (pH = 13.3), the sorption of Np(IV) was also shown to decrease at Glucconcentrations higher than 10 -6 M due to the formation of Np(IV)-Gluccomplexes. [109] For the reaction Np 4+ + Gluc -+ 4 H2O ⇌ Np(OH)4Gluc -+ 4 H + , logβ = -4.5(3) was deduced.…”
Section: Importance Of Complexing Agentsmentioning
confidence: 99%